CORRELATION OF POSSIBILITY AS A THEORETICAL AND REALITY AS A PRACTICAL IN LAW - Leyloyan, Hasmik (State and Law, 2023)
Analysis of the correlation between the categories "possibility" and "reality" makes it possible to penetrate into the essence of law, observe law in motion, identify patterns in the development of legal phenomena and realities, thus, foresee ways to introduce relevant legal regulatory mechanisms and improve the effectiveness of the implementation of law. In the article the author finds that the essence of the content of reality and possibility can be deeply disclosed, only in their relationship, where reality appears as a form or theoretical level, and possibility, as a material or practical level. The correlation between legal possibility and legal reality, the author is considered in various aspects of law, and gives special importance to the problem of differentiation between the concept of "legal reality" and "the real life in law". According to the conclusion presented in the article, legal reality is a materialized part of the legal system, but not all legal phenomena existing in the real life in law can be realized in legal reality and, so theoretical understanding of the problem of the correlation between reality and possibility in law, undoubtedly, has practical significance for increasing efficiency implementation of law in society.